PEMERIKSAAN STATUS GIZI DAN SKRINING ANEMIA PRAKONSEPSI PADA REMAJA PUTRI USIA SEBAGAI UPAYA DETEKSI DINI MASALAH KESEHATAN KRONIS - Winarsih Nur Ambarwati; Difa Maghfira Puti Nugraheni; Leyla Puput Novita Sari; Icha Aulya Praditaningrum (Universitas Muhammadiyah Surakarta, 2025)
Adolescence is a crucial period for growth and development. Health problems are one of the causes of growth and developmental disorders. The most common health problems experienced by adolescent girls, in particular, are malnutrition and anemia. Untreated anemia can become a chronic health problem in adolescents, affecting their current and future health. Undetected and untreated preconceptional malnutrition and anemia can progress to malnutrition (CED) and anemia in pregnant women. Anemia in pregnant women is often associated with poor pregnancy, birth, and child outcomes. Therefore, anemia screening in adolescents is crucial. However, this screening service is currently not routinely available. Providing the nutritional status examination and anemia screening activities by examining hemoglobin levels in grade XII female adolescents at SMK 2 Muhammadiyah Nguter Sukoharjo. Method: The method used to measure hemoglobin levels is the Cyanmethemoglobin method. Results: The results of anthropometric examinations showed that 14 students (51.85%) had good nutritional status and 13 students (48.1%) had poor nutritional status, consisting of 4 (14.8%) students experiencing obesity and 9 students (33.3%), including thin and very thin. The results of anemia screening showed that 17 students (62.9%) had anemia, and 10 students had normal hemoglobin levels (37.1%). Health check-up programs should be carried out routinely so that adolescents' health conditions can be monitored, and the results of the examinations need to be followed up by schools and community health centers through the provision of iron tablets, education, and guidance on healthy lifestyles by considering local cultural approaches.